Pengembangan Bahan Ajar Berbasis Media Interaktif Materi Teks Ceramah Kelas XI - Suyanti; Rita; Nila Safina (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and test the feasibility and determine the effectiveness of interactive media-based on teaching materials for class XI. The population from class XI SMAS Bani Adam Mabar as 79 students and the sample as 21 students. This study used development research that ausually called R&D (Research and Development) with 4D model. The procedure used four stages: (1) Define, (2) Design, (3) Develop, (4) Disseminate. The results indicated that Interactive Media-Based Teaching Materials for Class XI are very suitable in learning by previously through a validation test of 2 material experts and 2 media experts. The result of material expert I is 77%, material expert II is 89%, media expert I is 85% and media expert II is 75%. Furthermore, interactive media-based teaching materials for class XI were tested on 1 teacher of Indonesian language studies and 21 students of class XI in SMAS BANI ADAM Mabar. For trials on teachers in the field of study, the results were 83% or very good criteria, and for trials on students, the results were 92% or very good criteria. In addition, after the effectiveness test was carried out by providing evaluations to students, it was obtained that the students' scores reached the Minimum Completeness Criteria (KKM). Then it can be concluded that interactive media-based teaching materials for class XI are very feasible and effective to be used in learning.